1988
DOI: 10.1212/wnl.38.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic investigation in autosomal dominant limb‐girdle muscular dystrophy

Abstract: Limb-girdle muscular dystrophy is a syndrome of progressive myopathic weakness affecting shoulder and hip girdle and proximal arm and leg muscles. The disease occurs either sporadically or inherited as an autosomal recessive trait. Autosomal dominant inheritance is rare. We report a large family with apparent autosomal dominant inheritance. Sixteen members were affected with a disease characterized by proximal weakness, leg greater than arm, onset in the third decade, elevated CK and CK MB levels, and myopathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0
2

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 0 publications
1
57
0
2
Order By: Relevance
“…The phenotypic features of different MFMs are like those of muscular dystrophies, and some were first reported as such. For example, myotilinopathy was reported as limb girdle muscular dystrophy 1A by the clinical criteria, 36,37 and the ␣B-crystallinopathy of Canadian aboriginals was reported under the rubric of a fatal infantile muscular dystrophy. 38,39 Finally, the clinical and pathologic features of the FHL1 muscular dystrophies can be typical of MFMs, but MFM pathology has not been described or may have been overlooked in some cases of FHL1-related muscular dystrophies.…”
Section: Org)mentioning
confidence: 99%
“…The phenotypic features of different MFMs are like those of muscular dystrophies, and some were first reported as such. For example, myotilinopathy was reported as limb girdle muscular dystrophy 1A by the clinical criteria, 36,37 and the ␣B-crystallinopathy of Canadian aboriginals was reported under the rubric of a fatal infantile muscular dystrophy. 38,39 Finally, the clinical and pathologic features of the FHL1 muscular dystrophies can be typical of MFMs, but MFM pathology has not been described or may have been overlooked in some cases of FHL1-related muscular dystrophies.…”
Section: Org)mentioning
confidence: 99%
“…Also, different forms of MFM have the clinical features of muscular dystrophies and some were first reported as such. For example, myotilinopathy was first classified as LGMD1A by the clinical criteria [4,5] and zaspopathy [6,7] was first reported as a distal muscular dystrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, many types of muscular diseases are known, based on their clinical and histopathological aspects, and the molecular bases of most of them are elucidated (Weiler and al., 1999;Leturcq and Kaplan, 2000;Urtizberea, 2001;Authier et al, 2008). A particular interest in investigating these pathologies was raised in developed countries around 1980 following the era of advances in molecular genetics (Gilchrist and al., 1988;Beckmann et al, 1991;Ginjaar et al, 2000;Sandona and Betto, 2009). It has been shown that these pathologies derive from anomalies in proteins involved in muscle cell structures or functions.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of the proteins that are involved in this phenomenon explains the numerous types of myopathies. The majority of myopathies are genetically transmitted, in variable ways: autosomic, Xlinked, recessive, dominant (Eymard et al, 1997;Gilchrist et al, 1988;Bonne et al, 1999;Speer et al, 1999). In spite important similarities, differences also exist in their clinical expression.…”
Section: Introductionmentioning
confidence: 99%